Conditional risk of diverticulitis after non-operative management. Issue 13 (2nd September 2020) - Garfinkle, R; Almalki, T; Pelsser, V; Bonaffini, P; Reinhold, C; Morin, N; Vasilevsky, C-A; Liberman, A S; Boutros, M
Abstract: Background: The objective of this study was to describe conditional recurrence-free survival (RFS) of patients after an index episode of diverticulitis managed without surgery, and to estimate the difference in conditional RFS for diverticulitis according to specific risk factors. Methods: This was a multicentre retrospective cohort study including all patients managed without surgery for acute sigmoid diverticulitis at two university-affiliated hospitals in Montreal, Quebec, Canada. Conditional RFS for diverticulitis was estimated over 10 years of follow-up. A Cox proportional hazards model was performed at the index episode and again 2 years later. Results: In total, 991 patients were included for analysis. The 1, 2- and 3-year actuarial diverticulitis RFS rates were 81·1, 71·5 and 67·5 per cent respectively. Compared with the 1-year actuarial RFS rate of 81·1 per cent, the 1-year conditional RFS increased with each additional year survived recurrence-free, reaching 96·0 per cent after surviving the first 4 years recurrence-free. A similar phenomenon was observed for 2-year diverticulitis conditional RFS. Lower age (hazard ratio (HR) 0·98, 95 per cent c.i. 0·98 to 0·99), Charlson Co-morbidity Index score of 2 or above (HR 1·78, 1·32 to 2·39) and immunosuppression (HR 1·85, 1·38 to 2·48) were independently associated with recurrence of diverticulitis from the index episode. At 2 years from the index episode, immunosuppression was no longer associated with diverticulitis recurrence (HR 1·02, 0·50 to 2·09). Conclusion: The conditional RFS of patients with diverticulitis improved with each year that was survived recurrence-free. Although several factors at index presentation may be associated with early recurrence, the conditional probability of recurrence according to many of these risk factors converged with time. Graphical Abstract: Conditional recurrence-free survival for diverticulitis improved with each year survived recurrence-free. Although several factors at index presentation may be associated with early recurrence, the conditional probability of recurrence according to many of these risk factors converges with time. Operation unnecessary